2022
DOI: 10.1155/2022/9899548
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0139402 Promotes Bladder Cancer Progression by Regulating hsa-miR-326/PAX8 Signaling

Abstract: Background. Bladder cancer (BC) is a malignant and common malignant tumors. However, the prognosis of most patients with bladder cancer is still poor, and it is particularly important to identify early tumor diagnostic and treatment targets. Materials and Methods. High-throughput sequencing was used to evaluate the expression level of circRNA in bladder cancer tissue. MTT assay, wound healing assay, and transwell assay were used to detect the cancer cells’ proliferation, migration, and invasion affected by hsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Small RNA RNU6B (U6) (RiboBio, Guangzhou, China) was used as a control for the expression of miRNA ( Li et al, 2022a ). Primer sequences are summarized in previous studies, including miR-139-5p ( Li et al, 2022b ), hsa-miR-326 ( Wei et al, 2022 ), miR-10b-5p ( Niu et al, 2021 ), miR-500a-3p ( Long et al, 2022 ), and miR-592 ( Paul et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Small RNA RNU6B (U6) (RiboBio, Guangzhou, China) was used as a control for the expression of miRNA ( Li et al, 2022a ). Primer sequences are summarized in previous studies, including miR-139-5p ( Li et al, 2022b ), hsa-miR-326 ( Wei et al, 2022 ), miR-10b-5p ( Niu et al, 2021 ), miR-500a-3p ( Long et al, 2022 ), and miR-592 ( Paul et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…52 Moreover, studies have shown that Pax-8 promotes tumor cell proliferation, migration, invasion, and endothelial-mesenchymal transition (EMT) by targeting miR-144-3p and hsa_circ_0139402/hsa-miR-326. 52,53 Collectively, more investigation is necessary to fully comprehend how multiple factors cooperatively regulate Pax-8 expression. The specific molecular mechanism of translational or posttranslational regulation of Pax-8 needs to be further clarified.…”
Section: Regulation Of Pax-8mentioning
confidence: 99%
“…The luciferase assay further demonstrated that miR‐144‐3p directly targets the 3′ untranslated region (3′UTR) of the Pax‐8 gene to suppress its translation 52 . Moreover, studies have shown that Pax‐8 promotes tumor cell proliferation, migration, invasion, and endothelial‐mesenchymal transition (EMT) by targeting miR‐144‐3p and hsa_circ_0139402/hsa‐miR‐326 52,53 . Collectively, more investigation is necessary to fully comprehend how multiple factors cooperatively regulate Pax‐8 expression.…”
Section: Regulation Of Pax‐8mentioning
confidence: 99%
“…Bladder cancer (BLCA) ranks the ninth most common cancer globally, which is the most common malignancy of the urinary tract 1,2 . There are about 550 000 persons are newly diagnosed with BLCA and 200 000 persons died from this unfavorable disease in the world every year 3 .…”
Section: Introductionmentioning
confidence: 99%